2021
DOI: 10.1097/ncq.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Fall Prevention and Injury Reduction Utilizing Continuous Video Monitoring

Abstract: Background: Reduction of falls and fall-related injuries in hospital patients remains a priority. Consideration of technology via continuous video monitoring (CVM) is relevant for safe, quality care with favorable cost implications.Local Problem: Although fall rates were in the acceptable national safety standard guidelines, interventions were explored with the aim to further decrease falls using CVM. Methods: The quality improvement project collected descriptive statistics. Run charts portrayed data trends fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Davis et al 22 found that a VM program had a total estimated savings of approximately $88,000 during 6 weeks of study (equivalent to $762,667 annually), based on cost avoidance from sitter expenses and the cost related to avoided falls. A recent study from Hogan et al 29 found that 1 virtual sitter monitoring up to 10 patients resulted in a savings of 2,152 patient-hours of monitoring over 3 months. Based on the average hourly rate and benefits paid to sitters, the total cost savings was equivalent to more than $97,000 in sitter expenditure (equivalent to $388,000 annually).…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al 22 found that a VM program had a total estimated savings of approximately $88,000 during 6 weeks of study (equivalent to $762,667 annually), based on cost avoidance from sitter expenses and the cost related to avoided falls. A recent study from Hogan et al 29 found that 1 virtual sitter monitoring up to 10 patients resulted in a savings of 2,152 patient-hours of monitoring over 3 months. Based on the average hourly rate and benefits paid to sitters, the total cost savings was equivalent to more than $97,000 in sitter expenditure (equivalent to $388,000 annually).…”
Section: Discussionmentioning
confidence: 99%
“…23 Although widely used, empirical evidence supporting the addition of in-person sitters to standard fall precautions is scant. 23,24 RPM, an innovative technology that incorporates CVM, has been shown to promote patient safety 9 by reducing falls and subsequent injury. 5,9 RPM allows for increased monitoring of patients per observer as 1 RPM technician monitors 12 patients.…”
Section: Available Knowledgementioning
confidence: 99%
“…23,24 RPM, an innovative technology that incorporates CVM, has been shown to promote patient safety 9 by reducing falls and subsequent injury. 5,9 RPM allows for increased monitoring of patients per observer as 1 RPM technician monitors 12 patients. Patients can be redirected when they exhibit fall-risk behaviors, such as attempting to get out of bed without assistance.…”
Section: Available Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 5 years, video monitoring systems have demonstrated success in improving patient safety and reducing patient falls 9,10. EHH budgeted to implement a video monitoring system in July 2020.…”
Section: Video Monitoring Systemsmentioning
confidence: 99%